2008
DOI: 10.1017/s0033291708002961
|View full text |Cite
|
Sign up to set email alerts
|

The inability to ignore: distractibility in women with restricting anorexia nervosa

Abstract: Decreased ability to concentrate in the presence of explicit distracters is a feature of AN and is associated with longer duration of illness. This phenomenon could be addressed in psychological interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 54 publications
3
41
2
2
Order By: Relevance
“…Since the samples studied have primarily been adult samples (many of which have chronic illness histories), it remains a possibility that the deficits found are a ''scar'' effect of being unwell for a long time or indicate risk factors for the development of chronic AN. This is consistent with the observed positive relationship between distractibil-ity errors and duration of illness 17 and poor cognitive performance and frequency of hospital admissions. 12 One possible solution to this concern would be the recruitment of adolescents with brief histories of AN.…”
Section: Introductionsupporting
confidence: 91%
“…Since the samples studied have primarily been adult samples (many of which have chronic illness histories), it remains a possibility that the deficits found are a ''scar'' effect of being unwell for a long time or indicate risk factors for the development of chronic AN. This is consistent with the observed positive relationship between distractibil-ity errors and duration of illness 17 and poor cognitive performance and frequency of hospital admissions. 12 One possible solution to this concern would be the recruitment of adolescents with brief histories of AN.…”
Section: Introductionsupporting
confidence: 91%
“…No differences were found either in DOD or TMT, which means that participants with AN did not show verbal attention impairments, contrary to data reported by Kingston et al (1996) and Dickson et al (2008). Differences were found in SIP (Lauer et al, 1999) in cognitive tasks such as the SDMT, Stroop-W, and Stroop-C, but not in TMT-A, which includes a motor component.…”
Section: Attention and Speed Of Information Processingcontrasting
confidence: 85%
“…If it is considered that regardless of the task with which they are evaluated, such characteristics were observed, changes in selective attention could occur. This important finding is opposite to what some authors have mentioned about attentive difficulties being only observed when stimuli are related to food and body shape, as in the case of the Stroop Color and Word Test adapted for ED [16,46,47], and it also contradicts some research studies which indicate that alterations are found at the basic attention levels such as alertness and sustained attention [19,48]. This focusing on the details also reinforces the hypothesis of the existence of weaknesses in the central coherence process.…”
Section: Discussioncontrasting
confidence: 70%